Risk and returns to educational fields: A financial asset approach to vocational and academic education - Daniela Glocker; Johanna Storck (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Applying a financial assets approach, we analyze the returns and earnings risk of investments into different types of human capital. Even though the returns from investing in human capital are extensively studied, little is known about the properties of the returns to different types of human capital within a given educational path. Using information from the German Micro Census, we estimate the risk and returns to around 70 fields of education and differentiate between vocational and academic education. We identify fields of education that are efficient investment goods, i.e. high returns at a given level of risk, and fields that are chosen for other (non-monetary) reasons. Furthermore, we rank fields of education by their return per unit of risk and find that university education is not always superior to other educational paths.
Keywords: I21; J24; 330; Educational Choice; Human Capital Investment; Returns to Schooling; Mean-Variance Analysis